The Geographic Distribution of Saccharomyces cerevisiae Isolates within three Italian Neighboring Winemaking Regions Reveals Strong Differences in Yeast Abundance, Genetic Diversity and Industrial Strain Dissemination - Viel, Alessia; Legras, Jean-Luc; Nadai, Chiara; Carlot, Milena; Lombardi, Angiolella; Crespan, Manna; Migliaro, Daniele; Giacomini, Alessio; Corich, Viviana (Frontiers in Microbiology, 2017)
In recent years the interest for natural fermentations has been re-evaluated in terms of increasing the wine terroir and managing more sustainable winemaking practices. Therefore the level of yeast genetic variability and the abundance of Saccharomyces cerevisiae native populations in vineyard are becoming more and more crucial at both ecological and technological level. Among the factors that can influence the strain diversity, the commercial starter release that accidentally occur in the environment around the winery, has to be considered. In this study we led a wide scale investigation of S. cerevisiae genetic diversity and population structure in the vineyards of three neighboring winemaking regions of Protected Appellation of Origin, in North-East of Italy. Combining mtDNA RFLP and microsatellite markers analyses we evaluated 634 grape samples collected over three years. We could detect major differences in the presence of S. cerevisiae yeasts, according to the winemaking region. The population structures revealed specificities of yeast microbiota at vineyard scale, with a relative Appellation of Origin area homogeneity, and transition zones suggesting a geographic differentiation. Surprisingly, we found a widespread industrial yeast dissemination that was very high in the areas where the native yeast abundance was low. Although geographical distance is a key element involved in strain distribution, the high presence of industrial strains in vineyard reduced the differences between populations. This finding indicates that industrial yeast diffusion it is a real emergency and their presence strongly interferes with the natural yeast microbiota.